The Implementation of Canteen Management Policy in Sriwijaya University: A Qualitative Study - Rahmiwati, Anita; Febry, Fatmalina; Purnamasari, Indah; Etrawati, Fenny (Jurnal Ilmu Kesehatan Masyarakat, 2024)
A canteen in the campus environment is one of the infrastructures that educational units must own that will support educational activities if it is managed well by paying attention to the nutritional content of food and implementing proper hygiene and sanitation. This research aims to find an overview of the canteen management policy at Sriwijaya University. This research used a qualitative design with 23 research informants, consisting of 2 Vice Chancellors, 1 Dean, 2 Deputy Deans, 6 canteen owners, 6 employees, and 6 students at Sriwijaya University. Data collection was carried out using in-depth interviews and observation.The data was analyzed using the Content Analysis method and presented in a narrative for interpretation. Monitoring of each faculty’s canteen for the management of a healthy canteen has mainly been carried out by handlers or sellers. However, facilities and infrastructure, such as access to electricity, clean water, canteen area, and canteen location, still need to be improved. Regarding food quality, practices, and sanitation, the food sold in each canteen already has good nutritional content. The implementation of healthy canteen management policies has been regulated in policies per faculty, although it is not evenly distributed. It is stated that the central policy for managing healthy canteens is still being designed. The implementation of canteen management policies at Sriwijaya University is that facilities and infrastructure still need to be improved, he food handlers and canteen managers are expected to continue to pay attention to food hygiene and sanitation of canteen buildings by the Indonesian Minister of Health Regulation Number 1096 of 2011.